Perceived Organizational Support sebagai Mediasi dalam Peningkatan Kinerja Karyawan: Studi pada PT. BPR Bank Boyolali - Dyah Puspita Sari; Aulia Vidya Almadana (Faculty of Economics and Business Diponegoro University, 2026)
The regional banking industry plays an important role in supporting the local economy, but improving employee performance remains a major challenge in maintaining service quality and organizational competitiveness. Employee performance is influenced by various internal factors, including work engagement, job satisfaction, and perceived organizational support. This study aims to analyze the effect of work engagement and job satisfaction on employee performance with perceived organizational support as a mediating variable at PT BPR Bank Boyolali. This study is based on Social Exchange Theory, which explains that reciprocal relationships between employees and organizations can improve positive work attitudes and performance. This study uses a quantitative approach with a census method of all 132 employees of PT BPR Bank Boyolali. Data were collected through a questionnaire using a five-point Likert scale. Data analysis was performed using Structural Equation Modeling (SEM) based on Partial Least Square (PLS) with the help of SmartPLS version 4 software. Testing was carried out through outer model analysis to test validity and reliability, inner model analysis to see the relationship between variables, and mediation testing using indirect effects. The results of the study indicate that work engagement has a positive and significant effect on employee performance, and job satisfaction also has a positive and significant effect on employee performance. In addition, perceived organizational support has been proven to have a positive effect on employee performance and acts as a partial mediating variable in the relationship between work engagement and job satisfaction on employee performance. These findings indicate that improvements in employee performance are not only influenced by individual factors, but also by the extent to which the organization provides support, attention, and recognition to employees. Therefore, organizations need to strengthen work engagement, increase job satisfaction, and create consistent organizational support to improve employee performance.